2022
DOI: 10.1371/journal.pone.0262670
|View full text |Cite
|
Sign up to set email alerts
|

Towards an affect intensity regulation hypothesis: Systematic review and meta-analyses of the relationship between affective states and alcohol consumption

Abstract: While self-medication and positive and negative reinforcement models of alcohol use suggest that there is an association between daily affect and alcohol consumption, findings within the academic literature have been inconsistent. This pre-registered systematic review meta-analytically interrogated the results from studies amongst non-clinical populations that examine the relationship between daily affective states and alcohol consumption volume. PRISMA guided searches of PsychINFO, PsycARTICLES, Science Direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 148 publications
1
24
2
Order By: Relevance
“…As such, it may be that the apparent effect of experiences of stress or anxiety on consumption [ 21 ] are mediated by variation in alcohol-related beliefs. Indeed, this research links theoretically with the self-medication hypothesis [ 24 ] that posits that alcohol is used as a means of improving low mood and/or ameliorating negative affective state or mental/physical states (although see [ 25 ], which suggests that a model of affect intensity regulation may be a more advantageous way of understanding the alcohol-mood nexus, rather than theorising about mood valence). It also aligns with pre-COVID research by [ 26 ] indicating that coping, enhancement, and conformity, but not social, motives were associated with problem alcohol consumption in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it may be that the apparent effect of experiences of stress or anxiety on consumption [ 21 ] are mediated by variation in alcohol-related beliefs. Indeed, this research links theoretically with the self-medication hypothesis [ 24 ] that posits that alcohol is used as a means of improving low mood and/or ameliorating negative affective state or mental/physical states (although see [ 25 ], which suggests that a model of affect intensity regulation may be a more advantageous way of understanding the alcohol-mood nexus, rather than theorising about mood valence). It also aligns with pre-COVID research by [ 26 ] indicating that coping, enhancement, and conformity, but not social, motives were associated with problem alcohol consumption in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…We report how we determined our sample size, all data exclusions (if any), all manipulations, and all measures in the study. The design, methodology, hypotheses, and analyses of this study were preregistered on the Open Science Framework on the 2nd June 2020, after the commencement of data collection (https://osf.io/rphn4, Tovmasyan et al, 2020). Materials, data, and analysis code used in the study could also be found on the Open Science Framework (https://osf.io/dhk6j/, Tovmasyan et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…These accounts are supported by research highlighting associations between poor mental well-being and alcohol consumption (Appleton et al, 2018) and by work indicating a high degree of comorbidity between alcohol use disorders, anxiety, and depression (Brière et al, 2014; Burns & Teesson, 2002). However, research guided by such theories has also produced inconsistent findings across studies of both state (for a recent review see Tovmasyan et al, 2022) and trait negative affect. Some research utilizing measures of state negative affect point to a direct relationship between increased negative affect and elevated consumption (Austin et al, 2020; Mc Hugh & McBride, 2020; Mohr et al, 2005, 2020; O’Hara et al, 2014; Richardson et al, 2020; Simons et al, 2005, 2014) while others have found an inverse association (i.e., increased negative affect being associated with reduced consumption; Bresin & Fairbairn, 2019; de Leon et al, 2020; Dvorak et al, 2018; Rohsenow, 1982; Simons et al, 2010), or that there was no association (Duif et al, 2019; Dvorak & Simons, 2014).…”
Section: The Present Studymentioning
confidence: 99%
“…Alcohol consumption is influenced by emotional states 36 , and emerging evidence suggest an important role of clock genes in emotion regulation 37 . To identify potential links between emotional states and alcohol drinking, affective behaviors were assessed in mice of the current study before they were exposed to alcohol.…”
Section: Conflict Of Interestmentioning
confidence: 99%